2022
DOI: 10.1108/aaaj-11-2021-5529
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous practices of accounting on the ground: a Bourdieusian perspective

Abstract: PurposeThis study explores accounting practice in an Indigenous organization. This organization is embedded within a rural Aboriginal community in the country currently known as Australia. In doing so, this study illustrates the intertwining of accounting practice, practitioners, organizations and social/cultural context, while recognizing that the cultural embeddedness of accounting is not uniform.Design/methodology/approachEmpirical materials were collected as part of a qualitative field study with an Indige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…A small number of studies have conducted ethnographic research with First Nations organisations, such as Fukofuka et al (2023), Kalyta and Malsch (2018), Rossingh (2012) and Scobie et al (2023). These studies emphasise the value of deep immersion in fieldwork to observe accounting practices and accountability in intercultural settings (Fukofuka et al, 2023). Thus, this study responds to the call for further ethnographic enquiry in accounting.…”
Section: Citizen Activism Andmentioning
confidence: 96%
See 1 more Smart Citation
“…A small number of studies have conducted ethnographic research with First Nations organisations, such as Fukofuka et al (2023), Kalyta and Malsch (2018), Rossingh (2012) and Scobie et al (2023). These studies emphasise the value of deep immersion in fieldwork to observe accounting practices and accountability in intercultural settings (Fukofuka et al, 2023). Thus, this study responds to the call for further ethnographic enquiry in accounting.…”
Section: Citizen Activism Andmentioning
confidence: 96%
“…Previous ethnographic studies in accounting have explored a variety of organisational contexts and research settings (examples include Ahrens, 1997;Chua, 1995;Dey, 2007;Irvine, 2011). A small number of studies have conducted ethnographic research with First Nations organisations, such as Fukofuka et al (2023), Kalyta and Malsch (2018), Rossingh (2012) and Scobie et al (2023). These studies emphasise the value of deep immersion in fieldwork to observe accounting practices and accountability in intercultural settings (Fukofuka et al, 2023).…”
Section: Citizen Activism Andmentioning
confidence: 99%
“…They have various memberships outside the Church in that they belong to a village, have a daytime job and belong to families, all of which come to bear on how they act, interact and react in a religious setting. To that end, Fukofuka and Jacobs (2018), Fukofuka et al (2023), as well as Ahrens and Mollona (2007) showed how taking into account the complexity of the social agent provides richer insights into how and why they act, react and interact in a particular manner and with what consequences. Accordingly, our practice focus allows us to consider the multiple memberships of social agents and with what ramifications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also include in our understanding of indigeneity the deleterious effects of colonisation on indigenous peoples, which has led to the subjugation of indigenous worldviews, and in so doing acknowledge that sustainable finance research devoid of indigenous perspectives contributes to the continued colonisation of indigenous peoples. This is a view we adopt from the accounting discipline which is more advanced in its recognition of indigenous perspectives (Fukofuka et al, 2023). We extend our understanding of indigeneity to the definition of indigenous investments, more formally termed indigenous asset management, which we define as indigenous approaches to finance and investment taken by indigenous groups to advance their economic development using the assets and compensation that have been returned to them, by their respective governments, through processes of historical redress.…”
Section: Introductionmentioning
confidence: 99%